Modeling in vitro cholesterol reduction in relation to growth of probiotic Lactobacillus casei. (12th February 2013) - Kumar, Alok; Kumar, Mukesh; Ghosh, Moushumi; Ganguli, Abhijit
Abstract: Lactobacillus casei LA‐1 isolated from a nondairy fermented source was evaluated for its in vitro ability to reduce cholesterol. The bacterium tested positive for bile salt deconjugation in relation to cholesterol removal. Tested growth‐associated physiological variables such as pH, temperature and inoculum size were all found to have significant effects on in vitro cholesterol reduction and biomass production (both P < 0.005). Furthermore, a central composite design was used to evaluate the effects of significant variables and their interactions. A linear regression model was developed for in vitro cholesterol reduction as a function of growth‐associated variables. Maximum cholesterol reduction achieved was 45% whereas maximum biomass yield of 2.34 optical density was observed at the central point. Our study possibly indicates that the growth of L. casei LA‐1 depends on its cholesterol removing ability.